2013
DOI: 10.1121/1.4824908
|View full text |Cite
|
Sign up to set email alerts
|

Plumbing the depths of Ligeia: Considerations for depth sounding in Titan's hydrocarbon seas

Abstract: Saturn's moon Titan is the only satellite in this solar system with a dense atmosphere and hydrocarbon seas. The Titan Mare Explorer (TiME) mission would splashdown a capsule to float for 3 months on Ligeia Mare, a several-hundred-kilometer wide sea near Titan's north pole. Among TiME's scientific goals is the determination of the depth of Ligeia, to be achieved with an acoustic depth sounder. Since Titan's surface temperature is known to vary around 92 K, all instruments must be ruggedized to operate at cryog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In this work, I shown that the use of a realistic model, based on PC-SAFT, prevents the appearance of unphysical situations, like a speed of sound discontinuity, already noticed in previous published papers (Hagermann et al 2005;Arvelo & Lorenz 2013). However, even such sophisticated models need to be constrained by empirical data.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In this work, I shown that the use of a realistic model, based on PC-SAFT, prevents the appearance of unphysical situations, like a speed of sound discontinuity, already noticed in previous published papers (Hagermann et al 2005;Arvelo & Lorenz 2013). However, even such sophisticated models need to be constrained by empirical data.…”
Section: Resultsmentioning
confidence: 77%
“…However, they did not give the full derivation of the computed speed of sound. In the context of depths sounding, Arvelo & Lorenz (2013) made computations based on the speed of sound in cryogenic liquids. Their work also involves the NIST14 database.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sources should be similar to those common on Earth and include fracturing of cryo-and/or lithic-crust (quakes), explosive volcanism, debris flows/landslides, meteor impacts, and buoyant hydrothermal fluid plumes. Moreover, as is the case on Titan where there are open fluid lakes or seas, meteorological sound sources from precipitation, surface wave breaking, waterfalls, and wind-wave interaction can also be expected (Arvelo and Lorenz, 2013). Thus, the unique scientific contribution achieved by using hydrophones and hydroacoustic signal detection techniques on Earth is likely to be the same for other ocean worlds.…”
Section: Ocean World Geophysical Signals Recorded On a Hydrophonementioning
confidence: 99%
“…Note that the vertical extent of a 1 km hydrocarbon sea is small enough compared with Titan's radius (2,575 km) that gravity g can be considered constant with depth, in contrast to the deeper (~100 km) liquid water oceans of icy satellites like Europa, where g varies appreciably with depth (Leighton et al, 2013). Arvelo and Lorenz (2013) estimate acoustic signal loss due to sound absorption α in Titan's methane seas is expected to be very low (~0.035 dB km -1 measured at 20 kHz) and likely to have little effect on sound propagation.…”
Section: Figurementioning
confidence: 99%